Observation of Higgs Boson Decay to Bottom Quarks - (:unkn) unknown (AMER PHYSICAL SOC, 2018)
The observation of the standard model (SM) Higgs boson decay to a pair of bottom quarks is presented. The main contribution to this result is from processes in which Higgs bosons arc produced in association with a W or Z boson (VH), and are searched for in final states including 0, 1, or 2 charged leptons and two identified bottom quark jets. The results from the measurement of these processes in a data sample recorded by the CMS experiment in 2017, comprising 41.3 fb(-1) of proton-proton collisions at root s = 13 TeV, are described. When combined with previous VH measurements using data collected at root s = 7, 8, and 13 TeV, an excess of events is observed at m(H) = 125 GeV with a significance of 4.8 standard deviations, where the expectation for the SM Higgs boson is 4.9. The corresponding measured signal strength is 1.01 +/- 0.22. The combination of this result with searches by the CMS experiment for H -> b (b) over bar in other production processes yields an observed (expected) significance of 5.6 (5.5) standard deviations and a signal strength of 1.04 +/- 0.20.
Keywords: BROKEN SYMMETRIES; MODEL; PARTICLES; STRAHLUNG; PROGRAM; SEARCH; MASS